Protection of The Duties of The Notary's Office Towards Credit Guarantee Deeds of Certificates Which The Parties Refuse to Sign (Case Study Case Number 10/Pdt.G/2023/Pn.Pti) - Ariyani, Farida; Handoko, Widhi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Notaries are authorized to create authentic deeds under the Notary Law, including credit agreements secured by certificates to provide legal certainty for creditors and debtors. However, in practice, disputes often arise when one party reneges on their signature, as in Pati District Court Decision Number 10/Pdt.G/2023/PN.Pti. This situation emphasizes the need for legal protection for notaries who have carried out their duties in accordance with the provisions, so that they are not burdened with responsibility for the actions of parties who do not act in good faith. This study analyzes the protection of the notary's position and also analyzes the judge's considerations in the decision. This study uses a normative juridical approach, employing a statute approach and a case approach. This type of research is normative. The data sources and types are secondary data obtained through literature review. The analysis is prescriptive. The results show that in the legal protection of professional positions, a notary can undertake two legal protection measures: preventive measures to prevent disputes from arising, and repressive measures through the courts. In the judge's considerations in case number:10/Pdt.G/2023/Pn.Pti, emphasized that legal reasoning must be based on facts, evidence, and applicable legal regulations. This dispute stems from the plaintiff's claim that he never signed a power of attorney or credit guarantee deed. However, it was legally proven that there was a Special Power of Attorney dated February 28, 2013, signed by the plaintiff. Because the plaintiff could not prove any forgery of the signature, the lawsuit was rejected in its entirety by the panel of judges. This decision emphasizes the importance of the principle of legal certainty. As long as there is no criminal decision related to forgery, the deed and power of attorney remain valid. Keywords: Credit; Guarantee; Notary; Notarial Deed; Protection.